Programming Languages and Systems: 27th European Symposium on Programming, ESOP 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings - Amal Ahmed (Theoretical Computer Science and General Issues Series, 2018)
This book constitutes the proceedings of the 27th European Symposium on Programming, ESOP 2018, which took place in Thessaloniki, Greece in April 2018, held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018. The 36 papers presented in this volume were carefully reviewed and selected from 114 submissions. The papers are organized in topical sections named: language design; probabilistic programming; types and effects; concurrency; security; program verification; program analysis and automated verification; session types and concurrency; concurrency and distribution; and compiler verification.